Supplementation with sunflower seeds in beef cattle did not impact on oocyte and in vitro embryo production - Baltazar, A. L. [UNESP]; de Mattos, G. M.; Ropelli, B. M.; Firetti, S. M.G.; Castilho, C.; Pugliesi, G.; Maldonado, M. B.C. [UNESP]; Binelli, M.; Silva, J. O.F.; Lupatini, G. C. [UNESP]; Lafuente, B. S.; Membrive, C. M.B. [UNESP] (Wiley, 2018)
Supplementation with compounds rich in linoleic acid, including sunflower seed supplementation, promotes increase in conception rates in cows. We aimed to evaluate whether the sunflower seed (linoleic acid source) supplementation in beef donor females alters the plasma concentrations of cholesterol, triglycerides, HDL and LDL, increases the number and quality of oocytes, increases the cleavage rates and determines an improvement in number and quality of in vitro produced blastocysts. Thus, Nelore females were divided into two groups of 15 animals to receive supplementation with or without sunflower seed for 57 days. Females underwent follicular aspiration and the oocytes were subjected to in vitro embryo production. There was no difference (p >.1) between control group and group supplemented with sunflower seed on the number of displayed follicles; number of aspired oocytes; recovery rate; cleavage rate; number of embryos; number of blastocysts; embryos number of grades I and II; plasma concentrations of total cholesterol, triglycerides; HDL and LDL. Therefore, sunflower seed supplementation in oocyte donors did not increase the number and quality of oocytes, cleavage rates and the number and quality of blastocysts produced in vitro.
Keywords: cattle; embryonic structures; linoleic acid; oocytes; sunflower seed